Blockade of αEβ7 integrin suppresses accumulation of CD8+ and Th9 lymphocytes from patients with IBD in the inflamed gut in vivo. Issue 11 (19th August 2016) - Zundler, Sebastian; Schillinger, Daniela; Fischer, Anika; Atreya, Raja; López-Posadas, Rocío; Watson, Alastair; Neufert, Clemens; Atreya, Imke; Neurath, Markus F
Abstract : Objective: Therapeutically targeting lymphocyte adhesion is of increasing relevance in IBD. Yet, central aspects of the action of antiadhesion compounds are incompletely understood. We investigated the role of αEβ7 and α4β7 integrins and their blockade by vedolizumab and etrolizumab for trafficking of IBD T lymphocytes in an in vivo model of homing to and retention in the inflamed gut. Design: We explored integrin expression in patients with IBD by flow cytometry and immunohistochemistry, while regulation of integrins was studied in T cell cultures. The functional relevance of integrins was assessed by adhesion assays and a recently established humanised mouse model in dextran sodium sulfate-treated immunodeficient mice. Results: High expression of αEβ7 was noted on CD8 + and CD4 + Th9 cells, while α4β7 was expressed on CD8 +, Th2 and Th17 cells. T cell receptor stimulation and transforming growth factor β were key inducers of αEβ7 on human T cells, while butyric acid suppressed αEβ7. In comparison to α4β7 blockade via vedolizumab, blockade of β7 via etrolizumab surrogate antibody superiorly reduced colonic numbers of CD8 + and Th9 cells in vivo after 3 hours, while no difference was noted after 0.5 hours. AEβ7 expression was higher on CD8 + T cells from patients with IBD under vedolizumab therapy. Conclusions: AEβ7 is of key relevance for gut trafficking of IBD CD8 + T cells and CD4 + Th9 cells in vivo and mainly retention might account for this effect. These findings indicate that blockade of αEβ7 in addition to α4β7 may be particularly effective in intestinal disorders with expansion of CD8 + and Th9 cells such as IBD.